Examining the Impact of Job Satisfaction Dimensions on Employee Productivity: Evidence from Malaysia’s Manufacturing Industry - Rassiah, Kannan; Arumugam, Mohanavel; Azani, Noorhaslina (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: This study investigates the relationship between job satisfaction and employee productivity in the manufacturing sector in Selangor, Malaysia. The topic is significant as productivity is a key driver of organizational success, and understanding its link to job satisfaction can inform effective human resource strategies. Background Problems: The research addresses the question: How do dimensions of job satisfaction salary, job promotion, supervision, and co-worker relationships affect employee productivity in large manufacturing firms? Research Methods: A quantitative research design was employed using a structured questionnaire distributed to 108 respondents from major manufacturing companies in Selangor. Data were analyzed through descriptive statistics, Spearman’s rank correlation, and multiple linear regression to identify significant predictors of productivity. Finding/Results: The findings reveal that co-worker relationships have a significant positive impact on employee productivity, while salary, job promotion, and supervision do not show statistically significant effects. This suggests that interpersonal relationships and teamwork play a crucial role in enhancing performance. Conclusion: The study concludes that intrinsic and social motivators may influence productivity more than extrinsic factors such as compensation and promotion. Managers should prioritize strategies that foster supportive peer interactions and collaborative organizational cultures to build a more engaged workforce. Future research is recommended to examine moderating variables such as leadership style, work–life balance, and organizational culture for a deeper understanding of the job satisfaction–productivity nexus.